ATTRACTION OF FOREIGN INVESTMENTS AS AN ELEMENT OF ECONOMIC DIPLOMACY - Юлія Полякова; Оксана Шайда; Андрій Степанов (Економіка та суспільство)
The present article provides an analysis of the processes and features of attracting foreign direct investment as an important element of economic diplomacy, with a view to increasing the attractiveness and competitiveness of the country. This study examines the international experience of attracting foreign capital, with particular reference to the American, European, Asian and Arab investment models. An analysis of global foreign direct investment in 2023 was conducted, including the inflow of foreign investment in the top twenty countries. The article goes on to consider the economic diplomacy practised by a number of countries, including the United Kingdom, paying particular attention to the challenges currently affecting the investment attractiveness of Ukraine. It is noted that despite military threats, Ukraine has the potential to attract investment in strategic sectors. The authors propose mechanisms for intensifying investment processes in Ukraine within the framework of economic diplomacy, including improvement of legal regulation, development of public-private partnerships, and introduction of risk insurance mechanisms to increase trust on the part of foreign partners.